Local Wisdom Reflected in The Symbols in Masjid Saka Tunggal Banyumas - Ika Maratus Sholikhah; Dian Adiarti; Asrofin Nur Kholifah (IBDA': Jurnal Kebudayaan Islam, 2017)
This article discusses the heritage of Banyumas culture conserved by the inhabitants. Banyumas is famous not only for its tourist destination but also for its art performances such as begalan, lengger, calung, kentongan, and ebeg. One of the famous tourist destinations in Banyumas is a mosque called Masjid Saka Tunggal Baitussalam (MSTB). This research emphasizes on the description of MSTB as the heritage of Banyumas culture as well as explains the meanings and messages reflected in the symbols found in MSTB. This mosque was buit in 1288 and is the oldest mosque in Indonesia. The symbols were analyzed with semiotic theory using qualitative descriptive analysis. The data were gained through observation, documentation, and interviews. This research found that there were 13 symbols found in MSTB representing Islamic and Javanese philosophy, especially in spiritual activities. MSTB is a promising tourism site of Banyumas to be be developed as cultural heritage.